2008
DOI: 10.1097/rti.0b013e318156eb52
|View full text |Cite
|
Sign up to set email alerts
|

Chest CT of Incidental Breast Lesions

Abstract: Chest computed tomography (CT) is routinely used for the evaluation of diseases of the chest involving the lung, mediastinum, pleura, chest wall, and diaphragm. Benign and malignant breast lesions are not uncommonly encountered incidentally on chest CT. The chest CT radiologist should be aware of the different breast pathologies and their CT appearances as some can be diagnosed by chest CT, whereas others, such as breast cancer, should not be overlooked. The purpose of this pictorial essay is to show various c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…9 (17%) of 53 patients had abnormal ipsilateral axillary lymph nodes, with a longest-shortest axis diameter ratio of ,2 or an irregular or eccentric cortex [6]. Eight of these patients were subsequently found to have malignant lesions within the breast; however, only five patients had pathologically proven axillary lymph node metastases (see Figure 6), and, in three, the nodes were reactive or normal.…”
Section: Axillamentioning
confidence: 99%
See 1 more Smart Citation
“…9 (17%) of 53 patients had abnormal ipsilateral axillary lymph nodes, with a longest-shortest axis diameter ratio of ,2 or an irregular or eccentric cortex [6]. Eight of these patients were subsequently found to have malignant lesions within the breast; however, only five patients had pathologically proven axillary lymph node metastases (see Figure 6), and, in three, the nodes were reactive or normal.…”
Section: Axillamentioning
confidence: 99%
“…It has long been known that CT can identify incidental breast lesions when imaging for cardiac or respiratory disease [4]. Previous review articles have described the appearances of incidental breast lesions found on CT [5][6][7], but there has been no formal quantitative assessment of the impact of incidental CT-diagnosed breast lesions. With implementation of the Department of Health Cancer Reform Strategies, including the age extension to the NHS Breast Screening Programme (NHSBSP) [8] and cancer pathway targets [9], the workload of breast assessment units is rising.…”
mentioning
confidence: 99%
“…It is important that radiologists should not overlook breast lesions on chest CT and they should be aware of CT appearances of malignant and benign breast lesions (4).…”
Section: Introductionmentioning
confidence: 99%
“…Although many women participate in breast screening programs, multidetector computed tomography (MDCT) often provides the first images of the breast when patients undergo chest MDCT for evaluation of pulmonary or cardiac disease (1)(2)(3)(4). Since an MDCT scan provides improved contrast resolution, a larger field of view, and has cross sectional capability, breast lesions may be viewed more easily with a MDCT scan (1,5,6).…”
Section: Introductionmentioning
confidence: 99%